A Study on Awareness of Breast Cancer among Nursing Students - Tansushree. B1, Magendran.J2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Breast cancer is the most common type of cancer in women worldwide and its incidence is increasing in many countries. Breast cancer could happen to any woman irrespective of her education, social or cultural background. The lack of knowledge and incorrect perception about breast cancer prevention among females are responsible for the negative perception of the curability of cancer detected early and of the efficacy of the screening tests. It is, therefore, important to assess the level of awareness of risk factors in our communities. Therefore the present study is aimed to assess the awareness of breast cancer among nursing students. Methods: The present cross-sectional study was conducted among nursing students of SAVEETHA MEDICAL COLLEGE AND HOSPITAL, CHENNAI. A total of 150 nursing students were included in the study with their prior consent. The study period was from 21 st January 2019 to 30 the March 2019. Results: Our results showed insufficient knowledge of breast cancer among nursing students eventhough majority of them have heard of it. The results indicated the need for increased breast cancer awareness among university students. Conclusions: Our study participants did not have adequate knowledge on risk factors and symptoms of breast cancer .The implications of this study are to emphasize the need to teach nursing students breast cancer awareness and detection of breast cancer in the early stage their undergraduate courses